Development and Functional Characterization of Fetal Lung Organoids - Laube, Mandy; Pietsch, Soeren; Pannicke, Thomas; Thome, Ulrich H.; Fabian, Claire (Frontiers in Medicine, 2021)
Preterm infants frequently suffer from pulmonary complications due to a physiological and structural lung immaturity resulting in significant morbidity and mortality. Novel in vitro and in vivo models are required to study the underlying mechanisms of late lung maturation and to facilitate the development of new therapeutic strategies. Organoids recapitulate essential aspects of structural organization and possibly organ function, and can be used to model developmental and disease processes. We aimed at generating fetal lung organoids (LOs) and to functionally characterize this in vitro model in comparison to primary lung epithelial cells and lung explants ex vivo. LOs were generated with alveolar and endothelial cells from fetal rat lung tissue, using a Matrigel-gradient and air-liquid-interface culture conditions. Immunocytochemical analysis showed that the LOs consisted of polarized epithelial cell adhesion molecule (EpCAM)-positive cells with the apical membrane compartment facing the organoid lumen. Expression of the alveolar type 2 cell marker, RT2-70, and the Club cell marker, CC-10, were observed. Na+ transporter and surfactant protein mRNA expression were detected in the LOs. First time patch clamp analyses demonstrated the presence of several ion channels with specific electrophysiological properties, comparable to vital lung slices. Furthermore, the responsiveness of LOs to glucocorticoids was demonstrated. Finally, maturation of LOs induced by mesenchymal stem cells confirmed the convenience of the model to test and establish novel therapeutic strategies. The results showed that fetal LOs replicate key biological lung functions essential for lung maturation and therefore constitute a suitable in vitro model system to study lung development and related diseases.